The Role of microRNA in Ischemic and Hemorrhagic Stroke - Jolana, Lipkova; Kamil, Duris (Current drug delivery, 2017)
BACKGROUND: Stroke is the second leading cause of death worldwide. Understanding of gene expression dynamics could bring new approaches in diagnostics and therapy of stroke. Small noncoding molecules termed "microRNA" represent the most flexible network of gene expression regulators. METHOD: The aim of this review was to briefly describe the structure and function of microRNA and summarize the current knowledge about the involvement of microRNAs in the pathophysiology of ischemic and hemorrhagic stroke based on both experimental and clinical studies. RESULTS: Numerous profiling studies identified candidate microRNAs and partially described dynamics of their expression after the stroke. However, complex associations of specific microRNAs expression with main clinical characteristics and deeper insight into mechanisms of their regulatory functions are still missing. In this review, we put special emphasis on several microRNA clusters involved in neuroprotection (miR-124, miR-181, miR-21, miR-29, miR-210 and let7). Potential application of microRNAs as biomarkers and diagnostic or therapeutic targets was also discussed. CONCLUSION: Full understanding of the regulatory mechanisms of the microRNA networks represents a novel direction for stroke research. To date, we do not have effective tools to control pathophysiological processes associated with stroke. Thus the microRNAs have to be considered as a very promising target for future stroke therapies.
Keywords: zvířata; Brain Ischemia; biologické markery; Stroke; regulace genové exprese; hemorrgahic stroke; Gene Expression Regulation; thrombolysis; ischemic stroke; mikro RNA; ischemie mozku; Animals; Central nervous system; cévní mozková příhoda; microRNA; MicroRNAs; Biomarkers; lidé; Humans; embolectomies